Cepharanthine as an effective small cell lung cancer inhibitor: integrated insights from network pharmacology, RNA sequencing, and experimental validation - Zhao, Fengyun; Ding, Zhaowei; Chen, Mengting; Ji, Mingfang; Li, Fugui (Frontiers in Pharmacology, 2024)
Background Small cell lung cancer (SCLC) is an aggressive malignancy with limited treatment options and poor prognosis, underscoring the need for new therapeutic agents. Methods A library of 640 natural products was screened for anti-proliferative activity in SCLC cells. The effects of Cepharanthine (CE) on SCLC cells were assessed in vitro and in vivo. Network pharmacology and RNA sequencing (RNA-seq) were used to elucidate the molecular mechanisms. Pathway enrichment analysis was performed using Gene Set Enrichment Analysis (GSEA) with Hallmark and Reactome gene sets. Protein-protein interaction (PPI) networks, along with the Cytoscape cytoHubba plugin, were used to identify key hub genes. RT-PCR and Western blotting were employed to validate mRNA and protein expression. Molecular docking studies assessed the binding affinity of CE to potential targets. Bioinformatics analyses, including expression profiling, prognostic evaluation, and loss-of-function studies, were used to explore the role of specific genes in SCLC. Results CE was identified as a promising SCLC inhibitor. In vitro, CE significantly inhibited SCLC cell proliferation, colony formation, migration, and invasion, while promoting apoptosis. In vivo, CE treatment notably reduced tumor volume in xenograft models. Network pharmacology identified 60 potential target genes, with enrichment analysis indicating their involvement in cholesterol metabolism regulation. RNA-seq and experimental validation further confirmed that CE inhibits cholesterol synthesis in SCLC cells by downregulating key enzymes, including HMGCR, HMGCS1, IDI1, FDFT1, and SQLE. Molecular docking studies confirmed the binding of CE to these enzymes. Additionally, these enzymes were found to be highly expressed in SCLC cells, with elevated levels of HMGCS1, HMGCR, and IDI1 correlating with poor prognosis. Functional assays revealed that silencing these genes significantly suppressed SCLC cell proliferation. Conclusion This study identifies CE as a potential therapeutic agent for SCLC, acting through the suppression of cholesterol synthesis, and uncovers novel therapeutic targets for the treatment of this aggressive cancer.